Kualitas Semen dengan Berbagai Formulasi Pengencer Dasar Air Kelapa Hijau Selama Simpan Dingin pada Sapi Madura - Aulia Puspita Anugra Yekti; Jois Harsah; Muchamad Luthfi; Muhammad Dikman; Asri Nurul Huda; Kuswati Kuswati; Trinil Susilawati (Universitas Halu Oleo, 2018)
ABSTRAKInseminasi Buatan dengan menggunakan semen cair digunakan untuk daerah yang sulit nitrogen cair dan mempunyai kualitas yang lebih baik dari pada semen beku. Tujuan penelitian ini adalah untuk mengetahui kualitas berbagai bahan pengencer dasar air kelapa penyimpanan dingin 2-5°C.Penelitian ini dilaksanakan di Loka Penelitian Sapi Potong Grati, Pasuruan. Semen yang digunakan berasal dari sapi madura sebanyak dua ekor, berumur 5 dan 3 tahun dan berat badan yaitu 397 kg dan 360,5 kg. Sapi madura ditampung seminggu 2 kali dengan motilitas > 70% , sedangkan air kelapa yang digunakan adalah air kelapa hijau yang masih muda. Pengenceran semen cair dibagi menjadi 4 yaitu P0 (CEP-3 + 20% kuning telur) sebagai kontrol, P1 (air kelapa hijau +20% kuning telur), P2 (P1 + 0,4% putih telur + 1% fruktosa) dan P3 (P1 + 0,4% putih telur kuning telur +2% fruktosa). Data dianalisis menggunakan uji Pearson’s Chi Square dan Uji Deskriptif. Hasil penelitian menunjukkan motilitas spermatozoa sesuai standar SNI yaitu motilitas> 40% pada pengencer CEP-3 dapat disimpan selama hari ke-8 (40,50±6,43%) sedangkan pada pengencer dasar air kelapa hijau pada P1, P2 dan P3 tidak menunjukkan perbedaan yang nyata (P>0,05) selama disimpan 6 hari yaitu 40,50±10,12%, 38,00±4,22%, 40,00±8,50%. Abnormalitas dari semua perlakuan menunjukan nilai <20%. Viabilitas didapatkan nilai tertinggi pada perlakuan P0(89,58±2,16%) kemudian P1(89,39±3,79%), P2(88,62±4,59%) dan P3(87,93±4,41%).Kata kunci: CEP-3, semen cair, sapi madura, simpan dingin, air kelapa hijau ABSTRACTArtificial Insemination using liquid semen is performed for areas that where liquid nitrogen is difficult to find and havng better quality than frozen semen. Purpose of this research was to investigate the quality on various coconut water base diluents on liquid semen of madura bull during cold storage of 2-5°C. Research was conducted at Laboratory of Reproduction of Grati Beef Cattle Research Station, Pasuruan.Semen that is used comes from two madura bulls aged 5 and 3 years with body weight is 397 kg and 360.5 kg. The semen was collected twice a week with motility> 70%, and the coconut water used is unripe green coconut water. The research treatments were P0 (CEP-3 + 20% egg yolk) as control, P1 (unripe green coconut water + 20% egg yolk), P2 (P1+ 1% fructose + 0.4% egg white) and P3 (P1+ 0.4% egg white + 2% fructose). Data were analyzed using Pearson's Chi Square test and Descriptive Test. The results showed that the motility of spermatozoa was within Indonesian National Standard (SNI) with more than 40% motility in the CEP-3 diluent and it can be stored until the 8th day (40.50 ± 6.43%). The basic diluents of green coconut water at P1, P2 and P3 was not significantly affected (P> 0.05) until 6 days storing with the motility number average are 40.50 ± 10.12%, 38.00 ± 4.22%, 40, 00 ± 8.50%. The abnormality of all treatments was under 20%. The highest viability was showed by treatment P2 (89.58±2.16%), followed by P4 (89.39 ± 3.79%), P3 (88.62 ± 4.59%) and the lowest was P4 (87.93 ± 4.41%). Keywords:CEP-3, liquid semen, madura bull, cool storage, green coconut water ABSTRACT Artificial Insemination using liquid semen is performed for areas that where liquid nitrogen is difficult to find and havng better quality than frozen semen. Purpose of this research was to investigate the quality on various coconut water base diluents on liquid semen of madura bull during cold storage of 2-5°C. Research was conducted at Laboratory of Reproduction of Grati Beef Cattle Research Station, Pasuruan.Semen that is used comes from two madura bulls aged 5 and 3 years with body weight is 397 kg and 360.5 kg. The semen was collected twice a week with motility> 70%, and the coconut water used is unripe green coconut water. The research treatments were P0 (CEP-3 + 20% egg yolk) as control, P1 (unripe green coconut water + 20% egg yolk), P2 (P1+ 1% fructose + 0.4% egg white) and P3 (P1+ 0.4% egg white + 2% fructose). Data were analyzed using Pearson's Chi Square test and Descriptive Test. The results showed that the motility of spermatozoa was within Indonesian National Standard (SNI) with more than 40% motility in the CEP-3 diluent and it can be stored until the 8th day (40.50 ± 6.43%). The basic diluents of green coconut water at P1, P2 and P3 was not significantly affected (P> 0.05) until 6 days storing with the motility number average are 40.50 ± 10.12%, 38.00 ± 4.22%, 40, 00 ± 8.50%. The abnormality of all treatments was under 20%. The highest viability was showed by treatment P2 (89.58±2.16%), followed by P4 (89.39 ± 3.79%), P3 (88.62 ± 4.59%) and the lowest was P4 (87.93 ± 4.41%).